TA'TSIRUL USLUBI HAMMASI AL-MUTASALSILI ‘ALA MAHARATIL ISTIMIA' LITHULLABI AS-SHAFFI AL-AWWALI FIL MADRASATIS TSANAWIYYATIL ISLAMIYYATIL HUKUMIYYATI 1 LIMA PULUH KOTA - Izmi, Rahma Lailatul; Aisyah, Devy (Program Studi Pendidikan bahasa Arab IAIN Langsa, 2023)
The purpose of this study was to determine the effect of the chain whispering technique on the listening ability of grade 1 students at Madrasah Tsanawiyah Islamiyah Hukumiyah 1 fifty cities. And researchers used experimental research methods with three data collection instruments namely, through observation, interviews and exams / tests. The research design is a quasi experimental design with the type of the post-test only control group. And after the researcher used the physical chain technique on maharah istima', there was the highest score in maharah istima' learning, namely 100 and the lowest score was 46, then the researcher found that the value of to was greater than tt, namely 9.69 > 1.71. Therefore Ho is rejected and Ha is accepted, meaning that there is a difference between the learning value of maharah istima' using the chain whisper technique and the value of maharah istima' without using maharah istima'. The conclusion of this study is that the chain whisper technique has an effect on the learning value of maharah istima' in students.